Within these Shores : A Selection of Works from the Chantrey Bequest 1883-1985. - Graves Art Gallery, Sheffield (London : Tate Gallery, 1989)
Chantrey, Francis ; Farquharson, Joseph ; Logsdail, William ; Merritt, Anna Lea ; Ridley Corbet, Matthew ; Speed, Harold ; Clausen, George ; Alma-Tadema, Lawrence ; Shannon, Charles ; Philpot, Glyn ; Munnings, Alfred ; Cayley Robinson, Frederick ; etc.
Within these Shores : A Selection of Works from the Chantrey Bequest 1883-1985, exhibition at the Graves Art Gallery, Sheffield, 10 June - 2 September 1989
boek